Proton pump inhibitors in pediatric practice - Anna A. Shilova; Zajnab G. Alieva; Ol'ga A. Bashkina; Bela I. Kantemirova (Union of pediatricians of Russia, 2023)
The scientific review of the literature provides information on current clinical observations of the use of proton pump inhibitors in large randomized trials of Russian and foreign scientists, issues of their classification, pharmacokinetics, pharmacodynamics, pharmacogenetics, efficacy and safety of prescribing in pediatric practice, due to the growth of acid-dependent conditions in children and the need for further systematic research with the development of approaches to personalization of prescribing drugs for each age group.